Scratch-resistant lens and processing technology thereof

By forming a hard layer on the surface of the resin lens and plating an impermeable hybrid film layer, the problem of the resin lens being easily scratched is solved, efficient scratch resistance and durability is achieved, the service life of the lens is extended, and the cleaning is improved sex.

CN119307865APending Publication Date: 2025-01-14SEE WORLD OPTICAL CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411473975.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-22
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

Resin lenses are prone to scratches and breaks, and lack sufficient scratch resistance and durability.

Method used

By forming a hardened layer on the surface of the resin substrate and plating an impermeable hybrid film layer, including a silica film layer, a zirconium titanium mixture film layer, an ITO film layer and a superslip waterproof film layer, the electron gun and an ion source are used to evaporate together. Plating technology forms a film layer structure with optimized thickness and material combination.

Benefits of technology

It improves the scratch resistance and service life of the lens, the lens surface is smooth and easy to clean, and the anti-scraping performance is improved by more than 30%, extending the service life of the lens.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119307865A_ABST
    Figure CN119307865A_ABST
Patent Text Reader

Abstract

The invention discloses an anti-scraping lens and a processing technology thereof. The anti-scraping lens comprises a cured resin substrate, and a hardening layer is formed on the surface of the resin substrate through a sol-gel technology; the anti-reflection mixed film layers are plated on the front surface and the rear surface of the resin substrate, the anti-reflection mixed film layers sequentially comprise a silicon dioxide film layer, a zirconium-titanium mixture film layer, a silicon dioxide film layer, a zirconium-titanium mixture film layer, an ITO film layer, a silicon dioxide film layer and a super-smooth waterproof film layer from inside to outside, and the thickness of the anti-reflection mixed film layers on the front surface and the thickness of the anti-reflection mixed film layers on the rear surface are different. According to the invention, vacuum coating is carried out on the front surface and the back surface of the hardened lens, evaporation is carried out by adopting the electron gun and the ion source, and the anti-reflection mixed film layer is plated on the surface of the lens, so that high-standard protection is provided while the light transmittance is ensured, the service life of the glasses is prolonged as far as possible, and the lens is dirt-resistant and easy to clean.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of resin lenses, and in particular relates to a scratch-resistant lens and a processing technology thereof. Background Art

[0002] Resin lenses have the advantages of being light and impact-resistant, making them very suitable for general eyeglass wearers. They also have different refractive indices from low to high degrees, ranging from 1.499 to 1.67. The higher the refractive index, the thinner the lens and the lighter the weight. However, resin lenses also have their own defects, such as being easily scratched and broken. Therefore, there is an urgent need to invent a resin lens with high transmittance and scratch resistance. Summary of the invention

[0003] In view of this, the technical problem to be solved by the present invention is to provide a scratch-resistant lens and a processing technology thereof, so as to avoid the trouble of easy scratching of the lens in the past.

[0004] In order to solve the above technical problems, the present invention discloses a scratch-resistant lens, which comprises: After the resin substrate is cured, a hardening layer is formed on the surface of the resin substrate by a sol-gel process; The anti-reflective mixed film layers are plated on the front and back surfaces of the resin substrate, and the anti-reflective mixed film layers include, from the inside to the outside, a silicon dioxide film layer, a zirconium-titanium mixture film layer, a silicon dioxide film layer, a zirconium-titanium mixture film layer, an ITO film layer, a silicon dioxide film layer, and an ultra-smooth waterproof film layer, wherein the thickness of the anti-reflective mixed film layers on the front and back surfaces is different.

[0005] According to one embodiment of the present invention, the hardened layer is a silicone protective layer with a thickness of 2.5±0.5 um.

[0006] According to one embodiment of the present invention, the front side of the above-mentioned anti-reflection film layer is arranged from inside to outside as follows: the thickness of the silicon dioxide film layer is 30 to 60 nm, the thickness of the zirconium-titanium mixture film layer is 17 to 30 nm, the thickness of the silicon dioxide film layer is 17 to 35 nm, the thickness of the zirconium-titanium mixture film layer is 35 to 65 nm, the thickness of the ITO film layer is 4 to 7 nm, the thickness of the silicon dioxide film layer is 90 to 140 nm, and the thickness of the ultra-smooth waterproof film layer is 12 to 15 nm.

[0007] According to one embodiment of the present invention, the back side of the above-mentioned anti-reflection film layer is arranged from inside to outside as follows: the thickness of the silicon dioxide film layer is 30 to 60 nm, the thickness of the zirconium-titanium mixture film layer is 30 to 45 nm, the thickness of the silicon dioxide film layer is 27 to 40 nm, the thickness of the zirconium-titanium mixture film layer is 27 to 40 nm, the thickness of the ITO film layer is 4 to 7 nm, the thickness of the silicon dioxide film layer is 80 to 120 nm, and the thickness of the ultra-smooth waterproof film layer is 12 to 15 nm.

[0008] According to one embodiment of the present invention, the ultra-slip waterproof film layer is configured as a fluorine-containing polymer layer, which is evaporated onto the surface of the resin substrate by an electron gun, and the fluorine reacts with the silicon on the surface of the silicon dioxide film layer to form a bond.

[0009] The present invention also discloses a processing technology for a scratch-resistant lens, comprising: S1. Place the hardened and cured lens into a specific coating tool; S2. Place the tooling containing the lens in an oven at 60°C for heat preservation; S3. Put the insulated lens into the coating machine for coating; The S4 coating machine evacuates the vacuum chamber to below 4.0*10-5Torr while heating the vacuum chamber to 45°C. S5. Vacuum plasma cleaning; S6. Electron gun evaporation ion source assists the 1st to 6th film layers; S7. Electron gun evaporation deposition of the 7th layer of super-smooth waterproof film; S8. After the single-side coating is completed, the lens is turned over and process steps 1-7 are repeated; S9. After coating, the lens can be inspected and various performance tests can be performed in the laboratory.

[0010] According to one embodiment of the present invention, in the above step S6, first, in an Ar protective atmosphere, plasma assisted for 45 to 120 seconds, with an argon flow rate of 13 sccm, and then electron gun evaporation, ion source assisted, the coating layer is 6 layers in total, namely, silicon dioxide film layer, zirconium titanium mixture film layer, silicon dioxide film layer, zirconium titanium mixture film layer, ITO film layer, silicon dioxide film layer.

[0011] According to one embodiment of the present invention, the auxiliary voltage of the ion source is 140V±5, the current is 2.5A, and the oxygen is 20SCCM.

[0012] Compared with the prior art, the present invention can achieve the following technical effects: By vacuum coating the front and back of the hardened lens, using an electron gun and an ion source to co-evaporate, an anti-reflective hybrid film is applied to the lens surface to ensure light transmittance while providing high standards of protection, extending the service life of the glasses as much as possible. And there is an additional advantage: the smooth, scratch-resistant surface means the lens is dirt-resistant and easy to clean.

[0013] The coating manufacturing process is a special ion-assisted process for the lens. This single film layer compressed by advanced technology ensures good hardness and scratch resistance, which is about 30% higher than the Bayer value of resin lenses with traditional standard films.

[0014] Of course, any product implementing the present invention does not necessarily need to achieve all of the above-mentioned technical effects at the same time. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] The drawings described herein are used to provide a further understanding of the present invention and constitute a part of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings: Figure 1 Schematic diagram of a scratch-resistant lens according to an embodiment of the present invention. Figure ID

[0016] Resin substrate 10 , hardening layer 20 , silicon dioxide film layer 30 , zirconium-titanium mixture film layer 40 , silicon dioxide film layer 50 , zirconium-titanium mixture film layer 60 , ITO film layer 70 , silicon dioxide film layer 80 , super-smooth waterproof film layer 90 . DETAILED DESCRIPTION

[0017] The following will describe the implementation methods of the present invention in detail with reference to the accompanying drawings and embodiments, so that the implementation process of how the present invention applies technical means to solve technical problems and achieve technical effects can be fully understood and implemented accordingly.

[0018] Please refer to Figure 1 , Figure 1 Schematic diagram of a scratch-resistant lens according to an embodiment of the present invention.

[0019] As shown in the figure, a scratch-resistant lens comprises: a cured resin substrate 10, a hardening layer 20 formed on the surface of the resin substrate 10 by a sol-gel process; an anti-reflection mixed film layer coated on the front and back surfaces of the resin substrate 10, the anti-reflection mixed film layer comprising, from the inside to the outside, a silicon dioxide film layer 30, a zirconium-titanium mixture film layer 40, a silicon dioxide film layer 50, a zirconium-titanium mixture film layer 60, an ITO film layer 70, a silicon dioxide film layer 80, and an ultra-smooth waterproof film layer 90, wherein the thickness of the anti-reflection mixed film layer on the front and back surfaces is different.

[0020] In one embodiment of the present invention, the surface of the resin substrate 10 is hardened to form a dense hardened layer 20 to increase the surface hardness of the lens and improve its anti-fall and anti-scratch capabilities, and then the coating is performed. Preferably, the hardened layer 20 is an organic silicon protective layer formed by a sol-gel process with a thickness of 2.5±0.5um.

[0021] Furthermore, the coating layer is an anti-reflection mixed film layer, and 8 layers of films are stacked in sequence. It is deposited by evaporation using an electron gun and an ion source, and has a low refractive index film layer, a high refractive index film layer, the low refractive index film layer is silicon dioxide, the high refractive index film layer is a zirconium-titanium mixture film layer, and a thinner coating layer with anti-static function. The outermost layer is coated with an ultra-smooth waterproof, anti-fouling and oil-proof film layer.

[0022] Among them, the front anti-reflection film layer is arranged from inside to outside as follows: the thickness of the silicon dioxide film layer 30 is 30-60nm, the thickness of the zirconium-titanium mixture film layer 40 is 17-30nm, the thickness of the silicon dioxide film layer 50 is 17-35nm, the thickness of the zirconium-titanium mixture film layer 60 is 35-65nm, the thickness of the ITO film layer 70 is 4-7nm, the thickness of the silicon dioxide film layer 80 is 90-140nm, and the thickness of the ultra-smooth waterproof film layer 90 is 12-15nm.

[0023] Furthermore, the rear anti-reflection film layer is arranged from inside to outside as follows: the silicon dioxide film layer 30 has a thickness of 30 to 60 nm, the zirconium-titanium mixture film layer 40 has a thickness of 30 to 45 nm, the silicon dioxide film layer 50 has a thickness of 27 to 40 nm, the zirconium-titanium mixture film layer 60 has a thickness of 27 to 40 nm, the ITO film layer 70 has a thickness of 4 to 7 nm, the silicon dioxide film layer 80 has a thickness of 80 to 120 nm, and the ultra-smooth waterproof film layer 90 has a thickness of 12 to 15 nm.

[0024] The ultra-slippery waterproof film layer 90 is configured as a fluorine-containing polymer layer, which is evaporated onto the surface of the resin substrate by an electron gun. The fluorine reacts with the silicon on the surface of the silicon dioxide film layer to form a bonded surface with high hydrophobicity.

[0025] The present invention also discloses a processing technology for a scratch-resistant lens, comprising: S1. Place the hardened and cured lens into a specific coating tool; S2. Place the tooling containing the lens in an oven at 60°C for heat preservation; S3. Put the insulated lens into the coating machine for coating; The S4 coating machine evacuates the vacuum chamber to below 4.0*10-5Torr while heating the vacuum chamber to 45°C. S5. Vacuum plasma cleaning; S6. Electron gun evaporation assisted by ion source for the first to sixth film layers; first, in an Ar protective atmosphere, plasma assisted for 45 to 120 seconds, with an argon gas flow rate of 13 sccm, and then electron gun evaporation assisted by ion source, a total of 6 film layers, namely, silicon dioxide film layer, zirconium titanium mixture film layer, silicon dioxide film layer, zirconium titanium mixture film layer, ITO film layer, silicon dioxide film layer; S7. Electron gun evaporation deposition of the 7th layer of super-smooth waterproof film; S8. After the single-side coating is completed, the lens is turned over and process steps 1-7 are repeated; S9. After coating, the lens can be inspected and various performance tests can be performed in the laboratory.

[0026] The coating adopts vacuum coating technology, and its process is: 1.56, 1.60, 1.67 single hardened lenses are kept at 65℃, and the lenses are moved into the coating machine and vacuumed to below 4.0*10-5Torr, and the vacuum chamber is heated to 45℃. In the Ar protection atmosphere, plasma assisted 90~200s, the argon flow rate is about 13sccm, and then the electron gun evaporates the ion source to assist the coating layer for a total of 6 layers, and the electron gun evaporates the 7th layer of super-smooth waterproof film. The specific front surface process is shown in the table below:

[0027] See the table below for specific rear surface processes:

[0028] The measured blue film reflection spectrum values ​​of the front surface of the film layer of the resin lens processed by the above process are shown in the following table:

[0029] The green film reflection spectrum values ​​on the rear surface of the film layer are shown in the following table:

[0030] It can be seen that the lens undergoes a special ion-assisted process during the coating manufacturing process. This single film layer compressed by advanced technology ensures good hardness and a scratch resistance of about 30% higher than the Bayer value of resin lenses with traditional standard films. And there are additional advantages: the smooth, scratch-resistant surface means that the lens is dirt-resistant and easy to clean; at the same time, the film layer provides a high standard of protection against scratches, which prolongs the service life of the glasses as much as possible.

[0031] In addition to the above embodiments, the present invention may also have other implementations, 1. For example, the substrate may be a 1.499 substrate, a 1.552 substrate, a 1.600 acrylic substrate, a 1.600 MR-8 substrate, a 1.670 MR-7 substrate or a 1.710 substrate in addition to a 1.56 substrate; 2. A blue film on the front and back surfaces or a green film on the front and back surfaces. Any technical solution formed by equivalent replacement or equivalent transformation falls within the protection scope of the present invention.

[0032] The above description shows and describes several preferred embodiments of the present invention, but as mentioned above, it should be understood that the present invention is not limited to the form disclosed herein, and should not be regarded as excluding other embodiments, but can be used in various other combinations, modifications and environments, and can be modified within the scope of the invention concept described herein through the above teachings or the technology or knowledge of the relevant field. Changes and variations made by those skilled in the art do not depart from the spirit and scope of the present invention, and should be within the scope of protection of the claims attached to the present invention.

Claims

1. A scratch-resistant lens, characterized in that: include: A cured resin substrate, wherein a hardening layer is formed on the surface of the resin substrate by a sol-gel process; The anti-reflective mixed film layer is plated on the front and back surfaces of the resin substrate, and the anti-reflective mixed film layer includes, from the inside to the outside, a silicon dioxide film layer, a zirconium-titanium mixture film layer, a silicon dioxide film layer, a zirconium-titanium mixture film layer, an ITO film layer, a silicon dioxide film layer, and an ultra-smooth waterproof film layer, wherein the thickness of the anti-reflective mixed film layer on the front and back surfaces is different.

2. The scratch-resistant lens according to claim 1, characterized in that: The hardening layer is a silicone protective layer with a thickness of 2.5±0.5um.

3. The scratch-resistant lens according to claim 1, characterized in that: The front side of the antireflection film layer is arranged from inside to outside as follows: the silicon dioxide film layer has a thickness of 30 to 60 nm, the zirconium-titanium mixture film layer has a thickness of 17 to 30 nm, the silicon dioxide film layer has a thickness of 17 to 35 nm, the zirconium-titanium mixture film layer has a thickness of 35 to 65 nm, the ITO film layer has a thickness of 4 to 7 nm, the silicon dioxide film layer has a thickness of 90 to 140 nm, and the ultra-smooth waterproof film layer has a thickness of 12 to 15 nm.

4. The scratch-resistant lens according to claim 1, characterized in that: The back side of the anti-reflection film layer is arranged from inside to outside as follows: the silicon dioxide film layer has a thickness of 30 to 60 nm, the zirconium-titanium mixture film layer has a thickness of 30 to 45 nm, the silicon dioxide film layer has a thickness of 27 to 40 nm, the zirconium-titanium mixture film layer has a thickness of 27 to 40 nm, the ITO film layer has a thickness of 4 to 7 nm, the silicon dioxide film layer has a thickness of 80 to 120 nm, and the ultra-smooth waterproof film layer has a thickness of 12 to 15 nm.

5. The scratch-resistant lens according to claim 1, characterized in that: The ultra-slippery waterproof film layer is configured as a fluorine-containing polymer layer, which is evaporated onto the surface of the resin substrate by an electron gun, and the fluorine reacts with the silicon on the surface of the silicon dioxide film layer to form a bond.

6. A process for producing a scratch-resistant lens as claimed in claim 1, characterized in that: include: S1. Place the hardened and cured lens into a specific coating tool; S2. Place the tooling containing the lens in an oven at 60°C for heat preservation; S3. Put the insulated lens into the coating machine for coating; The S4 coating machine evacuates the vacuum chamber to below 4.0*10-5Torr while heating the vacuum chamber to 45°C. S5. Vacuum plasma cleaning; S6. Electron gun evaporation ion source assists the 1st to 6th film layers; S7. Electron gun evaporation deposition of the 7th layer of super-smooth waterproof film; S8. After the single-side coating is completed, the lens is turned over and process steps 1-7 are repeated; S9. After coating, the lens can be inspected and various performance tests can be performed in the laboratory.

7. The process for processing a scratch-resistant lens according to claim 6, characterized in that: In the step S6, firstly, in an Ar protective atmosphere, plasma assisted for 45 to 120 seconds with an argon flow rate of 13 sccm, and then electron gun evaporation was performed with an ion source assisted, and a total of 6 coating layers were formed, namely, a silicon dioxide film layer, a zirconium-titanium mixture film layer, a silicon dioxide film layer, a zirconium-titanium mixture film layer, an ITO film layer, and a silicon dioxide film layer.

8. The process for processing a scratch-resistant lens according to claim 7, characterized in that: The auxiliary voltage of the ion source is 140V±5, the current is 2.5A, and the oxygen is 20SCCM.

Citation Information

Cited By

  • Superhard scratch-resistant lens and preparation method thereof

    CN120742569A